Physical and electrochemical studies on nanocomposite -30 % PMMA-g-natural rubber (MG30) / Nurul Ilham Adam - Adam, Nurul Ilham (2013)
This thesis focuses on the effect of nanofillers on the physical and electrochemical properties of polymer electrolytes. 30% PMMA-g-natural rubber (MG30) is doped with lithium triflate (LiTf) salt and composited with silicon dioxide (SiO₂) or aluminum oxide (A1₂O₃ ) nanofiller. The conductivity of the samples is measured by impedance spectroscopy (IS) and shows a substantial increase in conductivity with the addition of lithium salt up to 35 wt. % after which, at higher salt loading (>35 wt.%) the conductivity seem to decrease. The optimum composition of MG30-LiTf salt complexes sample with highest conductivity is then separately composited with different concentrations of SiO₂ or A1₂O₃ filler…